A Simulation Analysis of the Net Effect of Feed Particle Size Distribution on SAG Mill Performance - Jaime E. Sepúlveda (Society for Mining, Metallurgy & Exploration, 2005)
Semiautogenous grinding (SAG) operators have been realizing the very significant impact of fresh feed particle size distribution on the mill grinding capacity. In actual practice, this impact may be quite difficult to assess because of the natural process variability that may also involve- concurrently other critical factors such as ore hardness. Recognizing the limitations of the empirical approach, the current publication proposes the use of mathematical models and simulators to explore and assess the net effect of feed particle size only, independent of any other factors. The simulation analysis here reported provides a basis to claim that the size distribution of the particles being ground (simply characterized by a % - 2" or similar measurement) is one of the most relevant controlling variables of the overall mill performance, regardless of the SAG circuit configuration.